Effects of aerobic exercise training on 24 hr profile of heart rate variability in female athletes - Pigozzi, F.; Alabiso, A.; Parisi, A.; Di Salvo, V.; Di Luigi, L.; Spataro, A.; Iellamo, F. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: The aim of this study was to investigate the effects of exercise training on autonomic regulation of heart rate under daily life conditions. METHODS: Twenty-six healthy female athletes (age 24.5+/-1.9 yrs) involved in regular physical activity were recruited during a period of yearly rest and randomly assigned to a five-week aerobic exercise training program (n=13) or to a non-exercise control group (n=13). Measures: before and after the five-week training, all subjects underwent a bycicle ergometer stress test and a 24-hour dynamic ECG monitoring. Autonomic regulation of heart rate has been investigated by means of both time and frequency domain analyses of heart rate variability (HRV). Spectral analysis of R-R interval variability (autoregressive algorithm) provided markers of sympathetic (low frequency, LF, 0.10 Hz) and parasympathetic (high frequency, HF, 0.25 Hz) modulation of the sinus node. RESULTS: Trained subjects showed a reduced heart rate response to submaximal workload. Before training there was no significant difference between the two groups. After training resting heart rate did not significantly differ between trained and untrained subjects. No significant differences were observed in the different time domain indexes of heart rate variability. The day-night difference in SD and SDRR were significantly less in the trained as compared to the untrained group. Normalized LF and HF components did not significantly differ between trained and untrained subjects, during the awake period. The decrease in the LF and the increase in the HF component during nighttime were significantly less in the trained group. The LF/HF ratio was significantly decreased during the night in the untrained group whereas it was not significantly different from the awake state in the trained group. CONCLUSIONS: These findings of the relative night-time increase in LF and the decrease in the day-night difference in time domain indexes of heart rate variability suggest that, in young female athletes, exercise training is able to induce an increase in the sympathetic modulation of the sinus node which may coexist with signs of relatively reduced, or unaffected, vagal modulation.